2022
DOI: 10.1055/a-1877-0594
|View full text |Cite
|
Sign up to set email alerts
|

Advantages of Revision Transforaminal Full-Endoscopic Spine Surgery in Patients who have Previously Undergone Posterior Spine Surgery

Abstract: Revision lumbar spine surgery via a posterior approach is more challenging than primary surgery because of epidural or perineural scar tissue. It demands more extensive removal of the posterior structures to confirm intact bony landmarks and could cause iatrogenic instability postoperatively; therefore, fusion surgery is often selected. However, adjacent segment disease after fusion surgery could be a problem, and further exposure of the posterior muscles could result in multiple operated back syndrome. To add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…First, by using the bony landmark at the lower pedicle, the process can be easily standardized, particularly for revision surgeries. Yagi et al reported variations in the accessing process depending on the severity of foraminal stenosis in revision surgeries [8]. In contrast, our proposed trans-pedicle approach demonstrates less variation and is easily applicable across cases.…”
Section: Discussionmentioning
confidence: 78%
“…First, by using the bony landmark at the lower pedicle, the process can be easily standardized, particularly for revision surgeries. Yagi et al reported variations in the accessing process depending on the severity of foraminal stenosis in revision surgeries [8]. In contrast, our proposed trans-pedicle approach demonstrates less variation and is easily applicable across cases.…”
Section: Discussionmentioning
confidence: 78%
“…In our series, we first treated all patients conservatively, with at least 2 selective nerve infiltrations under CT guidance to accurately identify the pain generator before considering operative interventions such as opening and endoscopic surgery. Opening resurgery for FBSS patients carries the potential risk of serious complications such as nerve damage, dura mater tear, delayed wound healing, infection, adjacent laminar degeneration, bone nonunion, bleeding, and many other complications [5]. For the above reasons, the minimally invasive nature, precise access, and effectiveness of endoscopic surgery are necessary in treating patients with FBSS, especially elderly patients.…”
Section: A a B B C Cmentioning
confidence: 99%
“…In such a situation, there is a requirement for minimally invasive intervention; full-endoscopic spine surgery (FESS) can meet this requirement, and there are cases where it can be performed under local anesthesia [4]. Also, compared to open surgery, FESS allows precise access to the location of the nerve structure that needs to be released while being able to pass through adherent fibrous tissue easily [5,6]. For these reasons, reoperation in patients with FBSS is more feasible and less risky.…”
Section: Introductionmentioning
confidence: 99%
“…When used for revision spine surgery, TELF and TELD are associated with minimal blood loss, lesser scar tissue formation, and similar operating time compared to primary spine surgeries [ 45 , 46 ]. In addition to other advantages of this technique, such as shorter operation time, minimal blood loss, and less muscle trauma, there are several published reports of transforaminal endoscopic spine surgery performed in awake patients under local anesthesia [ 47 , 48 ].…”
Section: Lumbar Spine Endoscopymentioning
confidence: 99%